2015
DOI: 10.1103/physrevd.91.083005
|View full text |Cite
|
Sign up to set email alerts
|

Post-Planck dark energy constraints

Abstract: Abstract. We constrain plausible dark energy models, parametrized by multiple candidate equation of state, using the recently published Cosmic Microwave Background (CMB) temperature anisotropy data from Planck together with the WMAP-9 low-ℓ polarization data and data from low redshift surveys. To circumvent the limitations of any particular equation of state towards describing all existing dark energy models, we work with three different equation of state covering a broader class of dark energy models and, hen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 94 publications
5
27
1
Order By: Relevance
“…It should be noted that the GCG model has been studied by many authors for the parameter range, 0 ≤ α ≤ 1 [17,18]. However, in this work, we have obtained the best fit values of the parameter A s and Ω m0 by fixing the value of other parameter α within the range, −1 < α < 0 (shown in Table 4), as α < 0, is in good agreement with the work of Sen and Scherrer [104], Gong [105] and Hazra et al [41]. It has also been noticed from Table 4 that the range of the allowed values of Ω m0 match well with the previous results obtained by Riess et al [106] and Sahni et al [107].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…It should be noted that the GCG model has been studied by many authors for the parameter range, 0 ≤ α ≤ 1 [17,18]. However, in this work, we have obtained the best fit values of the parameter A s and Ω m0 by fixing the value of other parameter α within the range, −1 < α < 0 (shown in Table 4), as α < 0, is in good agreement with the work of Sen and Scherrer [104], Gong [105] and Hazra et al [41]. It has also been noticed from Table 4 that the range of the allowed values of Ω m0 match well with the previous results obtained by Riess et al [106] and Sahni et al [107].…”
Section: Resultssupporting
confidence: 81%
“…It may be noted that the standard flat CDM model is represented by this parametrization with the choice of ω 0 = −1 and ω 1 = 0. In fact, many functional forms of f (z) have been considered in literature [33][34][35][36][37][38][39][40][41][42][43]. In this present work, we shall use four popular parametrizations of ω φ (z) to study the behavior of the deceleration parameter q(z) of this noncanonical scalar field model.…”
Section: Field Equations and Their Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the earlier results obtained by Hazra et al [13]. But with the addition of BICEP2 data, the improvement in χ 2 is roughly 4.3 for CPLDE models which is roughly three times of what one gets without BICEP2.…”
Section: T T Lsupporting
confidence: 93%
“…Initially considered as a natural candidate for a unification of dark matter and dark energy (UDM), it was later shown that this particular UDM behaviour is not suitable for the structure formation of the Universe [12]. But this fluid can be a possible dark energy candidate which tracks the background fluid initially and subsequently exits the tracking regime and starts acting as a dark energy candidate [13].…”
Section: Introductionmentioning
confidence: 99%